Functionalized d- and l-Arabino-Pyrrolidines as Potent and Selective Glycosidase Inhibitors - Haarr, Marianne B.; Lopéz, Óscar; Fernández-Bolaños, Jóse G.; Lindbäck, Emil; Sydnes, Magne O. (Synthesis, 2022)
The efficient synthesis of enantiomeric pairs of iminosugars including 1,4-dideoxy-1,4-imino-d-arabinitol (DAB) and 1,4-dideoxy-1,4-imino-l-arabinitol (LAB) analogues with an amidine, hydrazide, hydrazide imide, or amide oxime moiety is described. The preparation of DAB and LAB analogues commenced from l-xylose and d-xylose, respectively. The obtained iminosugars are tested against a panel of glycosidases with pharmaceutical relevance, revealing enhanced activity for the DAB analogues in comparison with the LAB analogues. In particular, the d-arabino-configured amidine behaved as a potent (submicromolar range) and selective inhibitor of α-mannosidase.
Keywords: iminosugars; glycosidase inhibitors; arabino; pyrrolidine; mannosidase